Political Economy of Rice Policy in Indonesia: A Perspective on the ASEAN Economic Opportunity - Arianto Patunru; Assyifa Szami Ilman (Center for Indonesian Policy Studies (CIPS), 2019)
For the majority of Indonesians, rice is a must in every meal. So important is rice that much of Indonesia's food security lies in this commodity. The government has intervened extensively and monopolised rice markets for decades, yet, Indonesians continue to be met with expensive rice prices at markets, and farmers struggle to build decent livelihoods for themselves. In this paper we discuss how the Indonesian government should explore the feasibility of solutions such as a commodity futures market to stabilise prices and support farmers to get a fair return on their harvests.
Keywords: 330; Indonesia rice policy; rice